Mitigation of Voltage Disturbances in PV Interconnected Grid Using ANFIS Based Dynamic Voltage Restorer - et. al, Suresh Penagaluru (International Journal of Advanced Science and Technology, 2020)
Abstract: In the past twenty years, with the speedy development of high technologies, new types of power equipment and various power electronic devices have been put into use in power systems. Consumer loads are very sensitive and requires more power quality than traditional electrical equipment. In order to alleviate these issues and to meet the load demand, renewable energy sources are the primary solution. It will give pollution free energy there by keeps environment safe for future generations. Integrating the renewable sources is the major issue. Regardless of whether the system is in normal steady state or faulted conditions, it is very necessary to ensure the availability of fundamental sinusoidal power with small amplitude deviation. In this paper a PV supported ANFIS based dynamic voltage restorer is proposed to deal with the power quality issues under various fault conditions. The performance of ANFIS-DVR  studied with PI control and ANFIS control. The performance is analyzed by using MAT LAB/SIMULINK Environment.